SODIUM–GLUCOSE COTRANSPORTER 2 INHIBITORS (SGLT2 INHIBITORS): CARDIOPROTECTIVE MECHANISMS AND CLINICAL EFFICACY IN HEART FAILURE - Ochilova Nigina (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Heart failure (HF) is becoming an increasingly serious healthcare challenge due to population aging and the rising prevalence of comorbid conditions. Although major advances in treatment have improved patient outcomes, HF continues to impose a substantial clinical and economic burden, highlighting the need for novel therapeutic strategies [1]. Sodium–glucose cotransporter 2 inhibitors (SGLT2 inhibitors) have recently emerged as a promising treatment option, demonstrating beneficial effects across the entire spectrum of HF, regardless of left ventricular ejection fraction (LVEF). This review explores the diverse mechanisms underlying the cardioprotective properties of SGLT2 inhibitors, including their ability to regulate energy metabolism, reduce oxidative stress, suppress inflammation, and promote autophagy. In addition, SGLT2 inhibitors shift myocardial energy utilization away from carbohydrates toward more energy-efficient substrates such as fatty acids and ketone bodies, thereby improving mitochondrial function and decreasing insulin resistance.